1988
DOI: 10.1161/01.cir.77.3.678
|View full text |Cite
|
Sign up to set email alerts
|

Mediation of reocclusion by thromboxane A2 and serotonin after thrombolysis with tissue-type plasminogen activator in a canine preparation of coronary thrombosis.

Abstract: Human recombinant tissue-type plasminogen activator (rt-PA) has been shown to be an effective and safe agent for coronary thrombolysis in patients with acute myocardial infarction. However, thrombolysis is associated with a high rate of acute reocclusion after discontinuation of rt-PA. The goals of the present study were to assess whether reocclusion after thrombolysis is caused by intracoronary platelet aggregation and to determine the role of thromboxane A2 (TxA2) No. 3, 678-684, 1988. CORONARY THROMBOL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 154 publications
(48 citation statements)
references
References 25 publications
5
43
0
Order By: Relevance
“…6 We have also shown that this phenomenon is primarily caused by intracoronary platelet activation and that TXA2 and serotonin cooperatively mediate reocclusion.6 SQ29548 and LY53857, given at the moment of reperfusion, were able to prevent this exclude the possibility that the interaction between SQ29548 and LY53857 observed in the present study may be pharmacokinetic and not pharmacodynamic (i.e., one antagonist had increased the plasma concentration of the other). However, this possibility seems very unlikely because LY53857 at half of the dose used in the present study35 and SQ29548 at a dose comparable to that used in the present study33'34 elicit a complete blockade of their respective receptors.…”
Section: Discussionsupporting
confidence: 48%
“…6 We have also shown that this phenomenon is primarily caused by intracoronary platelet activation and that TXA2 and serotonin cooperatively mediate reocclusion.6 SQ29548 and LY53857, given at the moment of reperfusion, were able to prevent this exclude the possibility that the interaction between SQ29548 and LY53857 observed in the present study may be pharmacokinetic and not pharmacodynamic (i.e., one antagonist had increased the plasma concentration of the other). However, this possibility seems very unlikely because LY53857 at half of the dose used in the present study35 and SQ29548 at a dose comparable to that used in the present study33'34 elicit a complete blockade of their respective receptors.…”
Section: Discussionsupporting
confidence: 48%
“…Similarly, after rt-PA induced thrombolysis, platelet activation and thromboxane are important mediators of vasomotor instability and reocclusion. 7,41 Although neither heparin7 nor aspirin'2 completely prevented reocclusion, intravenous aspirin did appear to facilitate reperfusion.…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, antagonists to the thromboxane A 2 or serotonin S 2 receptors led to facilitated thrombolysis or avoidance of reocclusion of the infarct vessel in experimental models. 30,31 Although these studies can, in retrospect, be viewed as classic, the pivotal role of platelets in this clinical setting and the potent pharmacological interventions were not fully appreciated or available until more than a decade later.…”
Section: Classic Studiesmentioning
confidence: 99%